Semiological Features of Nonepileptic Paroxysmal Events in Infancy - Ha Rim Noh; Young Hwan Kim; Kye Hyang Lee (Korean Child Neurology Society, 2020)
Purpose Nonepileptic paroxysmal events (NPEs) are common in infancy and may be misinterpreted as epileptic seizures. With a knowledge of common NPEs, they can usually be diagnosed based on a detailed history and examination. So far, no studies have explored the semiological presentations of NPEs in infancy without video electroencephalographic (VEEG) recordings. We aimed to describe the phenomenology of NPEs in infancy to provide useful information to clinicians, enabling easier diagnoses without VEEG studies. Methods We reviewed the medical records of 63 patients aged from 1 to 12 months diagnosed with NPEs at Daegu Catholic University Medical Center from September 2006 to June 2017. We classified the phenomenological features into five types: abnormal body movement, eye changes, breathing abnormalities, behavioral symptoms, and autonomic symptoms. Results Of the 63 patients, 37 were male and 26 were female. The mean age at onset was 6 months, and the mean duration of symptoms was 22.5 days. Abnormal body movements were the most common feature (88.9%), followed by eye changes (31.7%), autonomic symptoms (11.1%), breathing abnormalities (6.3%), and behavioral abnormalities (3.2%). The most common type of abnormal body movements was shivering-like movement (32.1%). Initially, 30 patients (47.6%) were diagnosed with unclassified NPEs, nine (14.3%) with sleep myoclonus, six (9.5%) with benign paroxysmal tonic upward gaze, and five (7.9%) with benign myoclonus of infancy. During follow-up, two patients (3.2%) were diagnosed with epilepsy. Conclusion Knowledge of the phenomenological characteristics of NPEs in infancy can be useful for making a correct diagnosis.